An improved solution to an optimal load flow problem - Muttiko, Chalerm (1975)
A method of optimizing the real and reactive power generation schedule and of solving the load flow simultaneously by VIRAY (12) is developed to obtain a fast and controlled convergence. The method unifies the field of nonlinear programming techniques and the Newton-Raphson method. A control of the convergence process is an addtional feature of the proposed method. By means of this control, the method converges for cases when the method made by VIRAY (12) or the normal Newton-Raphson method diverges. The feasibility of the method is shown by means of sample systems.
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Mimeographed.
Keywords: Motor buses -- Electric equipment; Electric power-plants -- Load